2021
DOI: 10.3390/gastroent12040041
|View full text |Cite
|
Sign up to set email alerts
|

The Role of EUS-Guided Drainage in the Management of Postoperative Fluid Collections after Pancreatobiliary Surgery

Abstract: Postoperative fluid collection (POFC) is a challenging complication following pancreatobiliary surgery. Traditional treatment with surgical drainage is associated with significant morbidity, while percutaneous drainage is associated with a higher rate of recurrence and the need for repeated interventions. Studies have shown that endoscopic ultrasound (EUS)-guided drainage may offer a promising solution to this problem. There are limited data on the ideal therapeutic protocol for EUS-guided drainage of POFC inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
(106 reference statements)
0
2
0
Order By: Relevance
“…In addition, operative outcomes and most postoperative complications were similar between the IS and FCSEMS groups, except for pancreatic fistula. Pancreatic fistula is a cautionary complication because it can lead to more severe consequences such as pseudoaneurysms, bleeding, tissue necrosis, and abscess formation [ 32 ]. Watanabe et al reported a general incidence of pancreatic fistula (grade B/C on International Study Group of Pancreatic Surgery) rate of 10.7% after PHCC surgery, which was closely related to a specific surgical maneuver intrapancreatic duct resection [ 31 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, operative outcomes and most postoperative complications were similar between the IS and FCSEMS groups, except for pancreatic fistula. Pancreatic fistula is a cautionary complication because it can lead to more severe consequences such as pseudoaneurysms, bleeding, tissue necrosis, and abscess formation [ 32 ]. Watanabe et al reported a general incidence of pancreatic fistula (grade B/C on International Study Group of Pancreatic Surgery) rate of 10.7% after PHCC surgery, which was closely related to a specific surgical maneuver intrapancreatic duct resection [ 31 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The endoscopic ultrasound-guided drainage showed a higher clinical success rate compared to percutaneous drainage. However, data on endoscopic ultrasound-guided drainage with LAMS were limited [ 27 ].…”
Section: Discussionmentioning
confidence: 99%